Analisis Lingkungan Kerja dan Disiplin Kerja Serta Pengaruhnya Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Intervening - Suwarto; Durotun Nasikah; Meisy Alda Putri (Universitas Muhammadiyah Metro, 2026)
This study aimed to find out whether the work environment affects employee performance. To find out whether work discipline affects the performance of the staff. To find out whether work motivation affects employee performance. Based on the sampling technique used, namely purposive sampling on employees of the metro city trade office, the number of samples used was 75 respondents. Data collection in this study uses a questionnaire, while the analysis technique in this study uses path analysis. The results of this study showed that (1) the work environment has a direct effect on work motivation with a tcal value of 8.448 > ttable 1.992. (2) Work discipline has a direct effect on work motivation with a tcal value of 2.908 > ttable 1.992. (3) The work environment has a direct effect on employee performance with a tcount value of 5.125 > ttable 1.992. (4) Work discipline has a direct effect on employee performance with a tcal value of 2.474 > ttable 1.992. (5) work motivation has a direct effect on employee performance with a tcal value of 3,340 > ttable 1,992.